A review of the effects of active learning on high order thinking skills: a meta-analysis within islamic education - Karwadi, Karwadi; Zakaria, Abd Razak; Syafii, Ahmad (Intelektual Pustaka Media Utama, 2024)
This study aims to ascertain the impact of the Active learning method on high-order thinking skills (HOTS) within the realm of Islamic education. Our primary contribution is the comprehensive meta-analysis of various preliminary and university educational studies. Using RStudio, we analyzed the differences in effect sizes, variations, and groups among studies. The findings indicate that the Active learning method significantly enhances HOTS, with the mixed learning method showing the most pronounced effect. We adopted a systematic approach, examining diverse learning methods like genre-based learning and blended learning model. Our research design entailed a meticulous meta-analysis of pre-existing literature rather than primary experimental or survey-based methods. However, we identified high heterogeneity in effect sizes as a limitation, suggesting the need for more nuanced studies in varied contexts. This research underscores educators' need to adapt learning strategies suited for specific educational levels, pointing towards a brighter horizon for tailored pedagogical interventions.